The Effect of Quality Service Towards Outpatients Satisfaction at Poasia Community Health Centre - Adryan Fristiohady; La Ode Muhammad Fitrawan; Yusniati Dwi Pemudi; Ruslin Ruslin; Sunandar Ihsan; Ruslan Ruslan; La Ode Muhammad Julian Purnama (Borneo Journal of Pharmacy, 2020)
The quality of outpatient services can be measured by the SERVQUAL model that considers five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study aimed to look at the effect of service quality on outpatient satisfaction at the Poasia community health center's pharmacy. The subjects in this study were 33 outpatients. The analysis technique used is gap analysis to compare patients' expectations and reality, normality test data based on questionnaire patient satisfaction tested for validation. This study's results indicate the average value of the gap in the Poasia community health center's pharmacy, amounting to -0.44. From the value of the gap, the lowest gap value in the pharmacy center of Poasia is the place of service and the provision of inadequate drug information of -0.88. Based on the paired t-test where a significant value >0.05, Ho is rejected, and Ha accepted, which means a significant difference between the quality of service and patients' satisfaction in the Pharmacy of Puskesmas Poasia Kendari City. This study concludes that there is a significant gap between expectations and reality at the Poasia community health center's pharmacy.